2009
DOI: 10.22358/jafs/66370/2009
|View full text |Cite
|
Sign up to set email alerts
|

The feeding and rearing systems of Iberian pigs affect the lipid composition and texture profile of dry-cured loin

Abstract: The effect of growing pigs on free-range (FR) or in confi nement with three different diets [acorn (A), acorn and grass (A-G) and formulated diet (FD)] was studied on the dry-cured loin lipid composition and texture profi le. Dry-cured loins from FR showed the highest proteolysis degree (estimated as nitrogen from free amino acid and ammonia) and the lowest hardness (P<0.05), whereas dry-cured loin from FD reached the lowest value of oleic acid (C18:1n-9). Principal component analysis permitted to separate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
3
3
0
Order By: Relevance
“…Our results seem to indicate a direct incorporation of C20:2n-6, so that this fatty acid presented higher contents in the loins from pigs with a higher intake of this fatty acid [5]. This fatty acid profile of total lipids was very similar to that previously reported in dry-cured loin [12,39,40]. In some of these studies, the effect of the different diets was also studied, obtaining a higher content in n-3 fatty acids using linseed and olive oils [39].…”
Section: Fatty Acidssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results seem to indicate a direct incorporation of C20:2n-6, so that this fatty acid presented higher contents in the loins from pigs with a higher intake of this fatty acid [5]. This fatty acid profile of total lipids was very similar to that previously reported in dry-cured loin [12,39,40]. In some of these studies, the effect of the different diets was also studied, obtaining a higher content in n-3 fatty acids using linseed and olive oils [39].…”
Section: Fatty Acidssupporting
confidence: 88%
“…In some of these studies, the effect of the different diets was also studied, obtaining a higher content in n-3 fatty acids using linseed and olive oils [39]. However, no effect on n-3 fatty acids was obtained using pasture and acorn, though a lower content in n-6 fatty acids was found [40]. Along the vacuum-packed storage the fatty acid profile remained constant and the minor differences obtained could be related to the variability between samples.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Thus, as observed in the moisture determination, RL samples have a higher amount of water, and, therefore, their hardness is reduced due to its influence, hence the result provided by the instrumental hardness is consistent. Moreover, these results are coherent with the literature, since previous studies showed that the dry-cured loins of pigs fed exclusively with natural resources had lower hardness values than those fed with natural resources and concentrates [1]. On the other hand, the resilience, which is the effort exerted by the sample to recover its original state, was higher for GL samples, which a priori, also seems coherent due to loins with higher moisture values would require less effort to recover their original height.…”
Section: Quality Parameters Of Dry-cured Loinssupporting
confidence: 91%
“…Meat products from the Iberian pig are highly valued by consumers, being the dry-cured loin one of the most recognized ones, due to its appreciated sensory characteristics and its lipid composition, with a reasonable amount in monounsaturated fatty acids [1]. Labelling of Iberian products have been regulated based on genetics and the rearing system of the animal [2], being classified in different commercial categories.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Maw et al [33] reported that hardness of the fat samples was related to fatty acid composition showing that increased softness was associated with increased linoleic and α-linolenic acids and decreased stearic and palmitic acid percentages. Soto et al [34] found that raising Iberian pigs indoor leads to harder dry cured loin probably due to low fat content, high SFA, low unsaturated fatty acids content and to a lower proteolysis degree. In this study WBS and hardness in meat and Soppressata salami were lower than those reported for meat from Cinta Senese and Iberian breed [16] [34] and for Italian salami [28] [29].…”
Section: Instrumental Texturementioning
confidence: 99%